Pretesting of the German Vocal Fatigue Index (VFI-D)-transcultural translation and cross validation - Stappenbeck, L E; Bohlender, J E; Brockmann-Bauser, M (HNO, 2020)
In clinical routine, vocal fatigue is a common symptom in patients with dysphonia. The aim of this study was to conduct a transcultural translation of the Vocal Fatigue Index (VFI), a standardized subjective questionnaire. Furthermore, pretesting and prevalidation were performed in 20 subjects, with comparison to the Voice Handicap Index (VHI‑9i) and the Vocal Tract Discomfort Scale (VTD). The translation, content review, and pretest of the German Vocal Fatigue Index (VFI-D) was divided into four sections: 1. transcultural translation, 2. expert voting on comprehensibility, 3. test of comprehensibility through cognitive interviews in 15 participants, 4. pretest of the VFI‑D with cross validation compared to VHI‑9i and VTD in 20 subjects. This process corresponds to current standards for transcultural translation and adaptation of questionnaires. According to expert voting and cognitive testing, the VFI‑D is correct and comprehensible (intercoder reliability κ = 0.66). The factor analysis revealed three distinguishable parts: VFI‑D part 1 correlates strongly with VHI‑9i and VTD, VFI‑D part 2 with VTD only (rho ≈ 0.800 each), and VFI‑D part 3 correlates only weakly with VHI‑9i and VTD (rho ≈ 0.585). Thus, convergence and divergence validity are proven. The first German version of the VFI‑D might be a base for further research on symptoms, causes, and treatment options in vocal fatigue. Particularly patients in voice-intensive professions may benefit.